Utilization of Kinemaster Application in Improving Learning Outcomes - Agus Sulaiman; Fauzan Muklis; Him Patry (International Journal of Language and Ubiquitous Learning, 2023)
Background. They are constrained by the network and do not have a HandPhone so that the video displayed during learning in the Zoom Meeting is sent back to the WhatSapp Group of class 3. Purpose. The purpose of this article is to find out what methods or media are suitable for students during the Covid-19 pandemic. Then the technology that can be utilized in the learning process so that educators and students can still meet virtually during the learning process. Method. The technique used in this investigation is an approximation technique by conducting a survey of the school before the online teaching process is carried out with the aim of seeing what kind of methods and media are used by educators at the elementary school. Then pay attention to the reaction of students at the first meeting of learning in this investigation. After that, analyze and find solutions so that learning runs effectively without discomfort and disinterest of students in the learning process. Results. In the first part, it can be recapitulated that 90% of learners cannot understand the learning provided through WhatSapp Group. In the second part, it can be recapitulated that 96% of students can understand the learning well, the learning process takes place through the Zoom Meeting application by displaying learning media in the form of videos created and edited using the KineMaster application. 4% of the learners experienced problems during the learning process. Conclusion. This investigation is detailed into 2 parts, in the first part, the application and the way of learning that is applied are not effective, in the second part all obstacles are corrected so that it can be concluded that the learning media created through the KineMaster application in the form of videos and shared through the Zoom Meeting application really causes a positive reaction to students.